The impact of digital technology on psychological treatments and their dissemination - Fairburn, Christopher G.; Patel, Vikram (Behaviour research and therapy, 2017)
The psychological treatment of mental health problems is beginning to undergo a sea-change driven by the widespread availability of digital technology. In this paper we provide an overview of the developments to date and those in the pipeline. We describe the various uses of digital interventions and consider their likely impact on clinical practice, clinical services and the global dissemination of psychological treatments. We note the importance of online clinics, blended treatment, digital assessment and digital training. •Psychological treatments are undergoing a sea-change driven by digital technology.•New forms of treatment are being developed.•Existing treatments are being converted into digital interventions.•Blended treatment is gaining in popularity and it can take a variety of forms.•Autonomous digital treatments have potential as public health interventions.